Risk Factors Associated With Echinococcosis in the General Chinese Population: A Meta-Analysis and Systematic Review - Zhang, Tiantian; Li, Bin; Liu, Yuying; Liu, Shou (Frontiers in Public Health, 2022)
Background: Echinococcosis is a severe zoonotic disease that imposes a substantial burden on human life. This meta-analysis aimed to summarize available data on the prevalence of human echinococcosis and identify the key risk factors for echinococcosis. Methods: Relevant studies were comprehensively searched in the PubMed, EMBASE, Web of Science, Cochrane, Chinese National Knowledge Infrastructure (CNKI), Chongqing VIP Information (VIP), Wanfang and SinoMed databases until August 22, 2020. A random-effects model was used to estimate the pooled odds ratio (OR) and 95% confidence interval (95% CI). The I2 and Q statistics were calculated to evaluate the heterogeneity, and potential sources of heterogeneity were identified using sensitivity analysis and subgroup analysis. Publication bias was estimated by funnel plots and Egger’s test. Results: A total of 1026 studies were identified through the database search, of which 26 were eligible for this meta-analysis. The pooled prevalence of AE and CE were 2.88% and 5.66%, respectively. Ethnicity (OR=2.93, 95% CI: 1.81-4.75; I2=0), being a herder (OR=2.66, 95% CI: 2.25-3.14; I2=8%), not washing hands before meals (OR=2.40, 95% CI: 1.34-4.28; I2=82.8%) and being female (OR=1.45, 95% CI: 1.26-1.66; I2=33.9%) were risk factors for AE. The top five risk factors for CE were ethnicity (OR=3.18, 95% CI: 1.55-6.52; I2=79.2%), nomadism (OR=2.71, 95% CI: 1.65-4.47; I2=55.8%), drinking nonboiled water (OR=2.47, 95% CI: 1.36-4.47; I2=85.7), feeding viscera to dogs (OR=2.35, 95% CI: 1.89-2.91; I2=21.5%), and being a herder (OR=2.19, 95% CI: 1.67-2.86; I2=85.1%). Conclusions: This study generalized articles that have contributed to our current understanding of the epidemic of human echinococcosis (AE and CE) in China over the years. The results support the ethnicity and dog-related factors are major risk factors for both CE and AE. The identification of echinococcosis risk factors may aid researchers and policymakers in improving surveillance and preventive measures aimed at reducing Echinococcus granulosus and Echinococcus multilocularis infection in humans.